Impact of marijuana legalization on cannabis-related visits to the emergency department. (4th May 2022) - Tolan, Nicole V.; Terebo, Tolumofe; Chai, Peter R.; Erickson, Timothy B.; Hayes, Bryan D.; Uljon, Sacha N.; Petrides, Athena K.; Demetriou, Christiana A.; Melanson, Stacy E. F.
Abstract: Background: Cannabis is widely used in the United States despite federal laws. In US states that have progressed toward legalization, there have been various reported impacts on cannabis-related emergency department (ED) visits. However, studies on the impact of legalization in Massachusetts (MA) EDs are lacking. Methods: Cannabinoid immunoassay (THC IA) results and cannabis-related ICD-10 codes were obtained for consecutive patient ED visits at two academic medical centers in Boston, MA over the following legalization periods (January 2012–December 2019): decriminalized (DEC), before medical dispensaries (MED BD), medical dispensaries available (MED DISP), before recreational dispensaries (REC BD) and recreational dispensaries available (REC DISP). Trends and monthly positivity rates for THC IA and ICD-10 codes were determined for these legalization periods. Results: There was an increase in both THC IA ( p < .0001) and cannabis-related ICD-10 codes ( p < .0001) in the ED as legalization progressed at both institutions. Positivity rates significantly increased by 7% for THC IA and 0.4% for ICD-10 codes. Increases in THC IA positivity were seen in females, patients aged 30–39, older adults (>59 years), and those in the highest income tertile. There was an increasing trend in amphetamine positivity and decreasing trend in opiate positivity in patients with positive THC IA. Unlike THC IA, significant trends per patient demographics were not seen with ICD-10 codes. Conclusions: Legalization of marijuana in MA has led to an increase in cannabis use as indicated by both increasing rates of positive THC IA results, in older adults, as well as increasing cannabis-related ICD-10 codes. Data suggest a steady increase in THC use associated with legalization that was not associated with an increase in opiate, fentanyl, or cocaine use. We recommend using ED THC IA positivity, an objective laboratory measure, to monitor THC use and the impact of state-specific progression in cannabis legalization.